Pegabdian Kepada Masyarakat di Pondok Pasantren Nafudatunnajah: PKM Yang dilakukan ini bertujuan untuk memberikan motivasi kepada siswa - siswa pada pasantren dengan memanfaatkan media digital sebagai sarana pembelajaran - Adzan Seknun; Akbar Valentino; Diski Apriana; Indri Junita Lestari; Idris cahyadi; Fauzan Respati Indira; Maulana Malik Ibrahim; Raja Alief Alkahfi; Tiara Oktaviani; Tifanny Patriane Andari (Abdi Jurnal Publikasi, 2023)
Technology in the world of education is a system that can be used to support various learning processes, so that it can produce a more effective and efficient learning process for students. And also can increase student interest in learning. Technology can also make it easier for teachers to provide more unique learning systems, as well as assist students in accessing quality learning resources. In Community Service (PKM) activities, at the Nafidatunnajah Islamic Boarding School, the service team has provided a glimpse of the use of digital media that can be used in the learning process, by utilizing several media or platforms that are frequently used, including Youtube, E-Learning, Canva and other media, to provide information directly to the students. It is intended that the students can use the media in their daily lives, so that it can help them learn and improve their abilities. Thus, this activity can have a positive impact on the students and the pesantren.